Patient Safety in Surgery - Clavien, Pierre-Alain; Stahel, Philip
Patient Safety in Surgery is an open access journal that publishes articles on all issues related to safety and quality of patient care in surgery and surgical subspecialties. The journal provides a scientific platform for specialists from all surgical fields and for other healthcare professionals to report, discuss, debate, and critically review all aspects related to errors, complications, and other safety issues in the management of patients undergoing surgical procedures. Morbidity and mortality in patients undergoing surgical procedures may, in large part, be preventable. The key to improving the management of adverse events in surgery is understanding their causes. These range from “simple” individual errors in surgical technique and perioperative decision making to system errors in hospitals, and extend as far as to general healthcare issues in politics. An evidence-based approach to quality improvement in surgical care must include the analysis of incidence and pattern of adverse events. This is particularly true for the analysis of procedures that did not result in an adverse event but had strong potential to, thus bearing the risk of these cases being neglected or trivialized, instead of being reported and reviewed as a “true” complication.